Employee onsite task assignment management and tracking app - Yeoh, Shin Yun (2023)
The modern workplace faces challenges concerning employee retention, productivity, and engagement. A need has been identified to address these issues through a structured task assignment and monitoring solution. Comprehensive research was undertaken, encompassing the study of relevant articles on employee task assignment and monitoring. Insights were further enriched through surveys and consultations with experts to understand the workplace challenges employers and employees encounter. This research resulted in creating an application comprising three pivotal modules: task assignment and monitoring, location tracking and reporting. These modules empower employers with the capability to allocate tasks, oversee employee progress, and trace their onsite location, along with facilitating report generation. The choice of Laravel and Flutter for the application development was grounded in their renowned attributes: ease of use, efficiency, and adaptability across platforms. The envisaged impact of this application is a significant uplift in productivity, engagement, and employee retention, fostering a conducive and healthy work culture. The devised application using Laravel and Flutter is a potent solution to the prevailing workplace challenges of employee task management and monitoring. By facilitating task assignment, progress tracking, and location reporting, this tool redefines workplace culture, bolstering productivity and engagement to the mutual advantage of both employees and employers.